Kelayakan Lead Apron sebagai Pelindung Paparan Radiasi Hambur - Asriningrum, Surdiyah; Ardiana, Ardiana; Muljana, Hayat; Musrifah, Musrifah; Ariyanto, Firlianti Dewi (Jurnal Imejing Diagnostik (JImeD), 2023)
Background: Lead apron constitutes one of the radiation protection devices available in the Radiology Department which is normally used in diagnostic and intervention radiology examinations to reduce the scattered radiation originating from the patient. The purpose of this study is to determine the physical condition, care, and maintenance of the lead apron. Methods: This research was quantitative research with survey methods at the Radiology Department of Al Islam Hospital Bandung and Al Islam Polytechnic Laboratory, Bandung. Results: The results suggested that the lead apron test at the Radiology Department of Al Islam Hospital Bandung contained 1 apron that had a leak with the covering area of 6458.67 mm2 and had to be rejected. The lead apron test at Al Islam Polytechnic Laboratory in Bandung contained 1 apron that had a leak with the covering area of 8750 mm2 and it had to be rejected. Conclusions: The lead apron at the Radiology Department of Al Islam Hospital Bandung and Al Islam Polytechnic Laboratory had one leak apron with the covering area of more than 670 mm 2 and had to be rejected. It is necessary to pay attention to the placement of the lead apron so that the lead apron is in good condition and can be used according to its function.